2020
DOI: 10.4103/ijo.ijo_1287_20
|View full text |Cite
|
Sign up to set email alerts
|

Presence of viral RNA of SARS-CoV-2 in conjunctival swab specimens of COVID-19 patients

Abstract: Purpose: To detect the presence of viral RNA of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) in conjunctival swab specimens of coronavirus disease-19 (COVID-19) patients. Methods: Forty-five COVID-19 patients positive for real-time reverse transcription-polymerase chain reaction (RT-PCR) for SARS-CoV-2 in nasopharyngeal swab with or without ocular manifestations were included in the study. The conjunctival swab of each patient was collected by an ophthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 12 publications
6
73
0
Order By: Relevance
“…One of the major conclusions which one can make from this systematic review is that the prevalence of ocular symptoms and signs is low and that conjunctivitis is a relatively rare occurrence. In this review, this prevalence ranges from 0 to 31.58% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This is in keeping with a previous large study from China which reported that nine patients (0.82%) out of 1099 laboratory-confirmed COVID-19 patients experienced conjunctival congestion [23].…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…One of the major conclusions which one can make from this systematic review is that the prevalence of ocular symptoms and signs is low and that conjunctivitis is a relatively rare occurrence. In this review, this prevalence ranges from 0 to 31.58% [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. This is in keeping with a previous large study from China which reported that nine patients (0.82%) out of 1099 laboratory-confirmed COVID-19 patients experienced conjunctival congestion [23].…”
Section: Resultssupporting
confidence: 86%
“…In this systematic review, apart from conjunctivitis, there were also descriptions of the development of pseudomembranous haemorrhagic conjunctivitis [13] and keratoconjunctivitis [15] in the patients. It was also suggested that ocular symptoms and signs commonly appear in patients with severe pneumonia [6]. The timing of the onset of ocular manifestations varied among the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] Also, reports suggesting red eye as the first feature of COVID-19 may have provoked patients to seek ophthalmologists' advise. [ 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 has been detected in different bodily fluids, including respiratory secretions, blood, and feces [8,9]. SARS-CoV-2 RNA has been detected by reverse transcription-polymerase chain reaction (RT-PCR) in the conjunctival secretions in a number of patients, and by viral culture in one patient in Rome [10][11][12][13][14][15][16][17][18][19][20][21]. Conjunctival secretions may, therefore, be a potential source of transmission of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%